Sustained transanorectal cryogenic treatment of hemorrhoids with the cryocure device: a prospective study - Kumar, Rajah Vijay; Franke, Hendrik R. (International Journal of Advances in Medicine, 2019)
Background: Globally about 330 million people suffer from hemorrhoids at some time during their lives. About 1.2 million new cases are reported annually, it is not discussed freely and a simple, safe and cost effective solution is yet to be proposed. The authors studied a new technique called Transanorectal Vasoconstriction as a possible treatment of grade 1, 2 and 3 hemorrhoids. Methods: The study randomly recruited 1591 patients suffering from grade 1 to 3 hemorrhoids in Europe and India and subjected them to Transanorectal Cryogenic Vasoconstriction technique using a device called Cryocure that provides sustained release cooling of hemorrhoids leading to vasoconstriction and shrinkage. The technique was applied between 7 and 15 days and patients were assessed after 3 months. Results: The treatment outcome of 1591 patients (M:F 962:629) recruited randomly, showed that 86.12% were practically symptom free after 7 to 14 days of the treatment, and during the assessment after three months. 6.36% of the treated patients reported that one or more symptoms of itching and pain persisted but were not bleeding after the treatment period of 7 to 14 days. A few patients, 3.11% had reported that they had no benefit whatsoever from the treatment. All patients were followed for a period of 9 months. However, it was found that 4.45% of patients had various types of recurrences including bleeding. Conclusions: The present study concludes that Transanorectal Cryogenic Vasoconstriction technique using Cryocure can be a simple, safe and cost effective choice of treatment in uncomplicated grade 1, 2 and 3 hemorrhoids.